O estruturalismo em livros didáticos: SMSG e matemática - curso moderno - Correia, Carlos Eduardo Félix [UNESP] (2015)
The goal of this research was to analyze how the structuralism has been present in the mathematics teachings proposal of two works for the Brazilian high school between the years of 1960 and 1970, being: the book 1 of the collection SMSG -School Mathematics Study Group - Mathematics for Junior High School Course and the book 1 of the work of Professor Osvaldo Sangiorgi Mathematics- Modern Course for Junior High School. Both began to diffuse in Brazil from 1964. We have taken by methodological referential the hermeneutics of profundity proposed by Thompson (1995) in three dimensions of analysis: Social-Historic analysis, formal analysis or discursive analysis and the interpretation-reinterpretation. We agree with Oliveira (2008) that the didactics books can be considered as Symbolic Forms and, thus, are passive of several interpretations. We have concluded that the structuralism has been present in the two analyzed works. In the book of SMSG, under the light of logic, by the method of reasoning to the construction of the mathematics concepts, in this, the students are led to a way of structuring the reason the think the mathematics by the logical principle of deduction. In the book of Sangiorgi, under the light of formalism, approaching the ideas proposed by Bourbaki, in his work Elements of mathematics which demonstrate the concern with the axiomatic exposition that proceeds from the general to the private in a depurated presentation, a profound unit that lies on the Theory of Sets and hierarchical in terms of abstract structures. The authors concerns with the conceptual pre-requisites, obeying the phase of the construction of the mathematical knowledge and observing, above all, values, attitudes, anxieties, abilities and motivation, attests also the presence of the psychological structuralism of Piaget in both works